(untitled) (Medico Legal Update, 2020)
The high prevalence of high-risk pregnancies, which can lead to premature delivery, contributes to an increase in the rates of preterm and low-birth weight (LBW) infants, with an increase in the number of cesarean deliveries. This study was done to access maternal variables and their associations with cesarean deliveries of LBW newborns. A retrospective study was conducted by reviewing the medical records of pregnant women who underwent cesarean sections for the delivery of LBW infants (weight, ?1500 and 35 weeks at delivery, and 50.8% attended less than eight prenatal consultations. Hypertensive syndrome (23.8%) was the main indication for cesarean delivery. Among the newborns, 58.3% had an Apgar score of 7 in the first minute of life, 79.3% had a score of 9 in the fifth minute of life, and 54.3% were females. Conclusions: Several maternal variables such as primiparity, education level, number of prenatal consultations, and presence of maternal hypertensive syndrome had a statistically significant association with the occurrence of cesarean sections for the delivery of LBW infants.